2014
DOI: 10.1007/s12011-014-0110-9
|View full text |Cite
|
Sign up to set email alerts
|

Liver Toxicity of Thioacetamide is Increased by Hepatocellular Iron Overload

Abstract: An increase in hepatic iron concentration might exacerbate liver injury. However, it is unknown whether hepatic iron overload may exacerbate acute liver injury from various toxins. Therefore, we evaluated how manipulations to increase hepatic iron concentration affected the extent of acute liver injury from thioacetamide. In this study, we used rats with either "normal" or increased hepatic iron concentration. Iron overload was induced by either providing excess iron in the diet or by injecting iron subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…To assess the potential benefit of combined screening for cell death, MMP activity, and transferrin receptor expression on the detection of DILI, we used fluorescent imaging probes specific for these biomarkers (AV-750, MMP-645, and TfV-750, respectively) to image the livers of animals receiving four different liver injury–inducing chemical compounds. Two of these compounds (TAA and APAP) are known to induce hepatocellular injury (McGill et al, 2012; Ackerman et al, 2015), a third drug (RMP) predominantly induces liver cholestasis (Zítková et al, 1982; Katz and Lor, 1986; Zargar et al, 1990), and a fourth drug (CPZ) induces mixed hepatocellular/cholestasis injury (Mullock et al, 1983). Serum ALT/ALP ratios can provide a rough mechanistic assessment, with hepatocellular injury defined as a ratio > 5, cholestasis as a ratio < 2, and mixed hepatocellular/cholestasis with a ratio between 2 and 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the potential benefit of combined screening for cell death, MMP activity, and transferrin receptor expression on the detection of DILI, we used fluorescent imaging probes specific for these biomarkers (AV-750, MMP-645, and TfV-750, respectively) to image the livers of animals receiving four different liver injury–inducing chemical compounds. Two of these compounds (TAA and APAP) are known to induce hepatocellular injury (McGill et al, 2012; Ackerman et al, 2015), a third drug (RMP) predominantly induces liver cholestasis (Zítková et al, 1982; Katz and Lor, 1986; Zargar et al, 1990), and a fourth drug (CPZ) induces mixed hepatocellular/cholestasis injury (Mullock et al, 1983). Serum ALT/ALP ratios can provide a rough mechanistic assessment, with hepatocellular injury defined as a ratio > 5, cholestasis as a ratio < 2, and mixed hepatocellular/cholestasis with a ratio between 2 and 5.…”
Section: Resultsmentioning
confidence: 99%
“…TAA is an organosulfur compound that has been used as a substitute for hydrogen sulfide, as a stabilizer of motor fuel, and as a topical preventative for mold growth on fruit. It is known as a class 2B carcinogen that also induces marked hepatocellular toxicity in animals (Wang et al, 2004; Ackerman et al, 2015). RMP is a widely used antimicrobial agent that is a crucial component in treatment regimens for tuberculosis.…”
Section: Methodsmentioning
confidence: 99%
“…Compromised tissue repair in diabetic models highly influences TAA hepatotoxicity, as in streptozotocin (STZ)‐induced diabetic rats prolonged liver injury increases TAA hepatotoxicity (Wang, Fontenot, Soni, Bucci, & Mehendale, ). However, an in vivo study on rats showed that TAA toxicity could be exacerbated by hepatic iron overload (Ackerman, Pappo, Link, Glazer, & Grozovski, ).…”
Section: Means Of Chemical Modulation Of Hepatic Apoptosismentioning
confidence: 99%
“…All rats were maintained on standard rat chow diet (SRCD; pellets #19520; Koffolk, Tel Aviv, Israel) and were given tap water to drink ad libitum. The composition of SRCD is reported elsewhere (Ackerman et al 2015).…”
Section: Experimental Designmentioning
confidence: 99%